Penerapan Teori Triangle Dalam Mendeteksi Kecurangan Laporan Keuangan - Fazria, Rizka; Lubis, Salsabila Azzahro; Fadilah, Alma Hafsa; Nayma, Salshabilla; Azzahra, An Suci (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyse the application of Fraud Triangle Theory in detecting financial statement fraud through a literature study of 20 scientific articles published in 2023-2024. The Fraud Triangle Theory developed by Donald R. Cressey highlights three main elements that cause fraud, namely pressure, opportunity, and rationalisation, all of which must be present for fraud to occur. Based on analysis of the selected articles, it was found that pressure, both internal and external, was the main driver of financial statement fraud, with 19 out of 20 articles stating a significant influence. The element of opportunity was also consistently identified as an important factor, where weaknesses in internal control opened up space for financial manipulation. Meanwhile, rationalisation plays a role in morally or ethically justifying fraudulent acts. This study confirms that the three elements of Fraud Triangle Theory significantly influence the occurrence of financial statement fraud and provides recommendations for future fraud detection models to focus more on identifying indicators of pressure, opportunity and rationalisation in the company's internal control system to effectively improve fraud prevention and early detection